SOLID HYDROCARBONS IN PROTEROZOIC DOLOMITES, TAOUDENI BASIN, MAURITANIA. (January 2016) - Albert‐Villanueva, E.; Permanyer, A.; Tritlla, J.; Levresse, G.; Salas, R.
Abstract : The Taoudeni Basin (Mauritania / Mali, West Africa) was formed as a result of pre‐ Pan‐African subsidence associated with rifting at the margins of the West African craton. Hydrocarbons in the Taoudeni Basin are derived from source rocks in the Meso‐Neoproterozoic Atar Group, which is composed of facies varying from stromatolite‐dominated carbonates to organic‐rich basinal shales. The stromatolitic carbonates are dolomitized and contain solid hydrocarbons (pyrobitumen). The pyrobitumen was formed in response to a Mesozoic hydrothermal event, with peak temperatures locally reaching 380°C, which resulted in hydraulic fracturing of the carbonates. Gas shows were recorded from these carbonates in the Abolag‐1 well and suggest that they may have potential as a reservoir rock. For this study, samples of Atar Group dolostones and black shales were collected from two localities in the Mauritanian part of the Taoudeni Basin and were analyzed by means of various geochemical and microscope‐based techniques including fluid inclusion analyses. The study suggests that Meso‐Neoproterozoic source rocks generated oil and gas during the Late Neoproterozoic – Early Palaeozoic. Later, in the Jurassic, a hydrothermal event caused in‐reservoir thermal cracking of the hydrocarbons to pyrobitumen and a second phase of gas generation and migration.